RANCANG BANGUN DAN ANALISIS KINERJA LAMPU TIDUR OTOMATIS BERBASIS SENSOR LDR - Ramon Panca Lasmna; Muhammad Erlangga; Ikhsan Ramadhan; Ferdi Ferdi; Delita M Puteri (LPPM Politeknik Pajajaran ICB Bandung, 2025)
A night light is a low-intensity lighting device designed to provide visual comfort in the dark. The research methodology includes designing an electronic circuit, placing the LDR sensor as an input element, and testing the system's effectiveness at various light levels. Parameters analyzed include the sensor's reaction to changes in light, the system's reliability in turning the light on and off, and its energy efficiency. The test results indicate that the system can operate automatically and stably, with a fairly good response to fluctuations in ambient light intensity. The lamp is optimally activated in dark situations and deactivated when exposed to bright light, providing the potential to improve energy efficiency and user comfort. Thus, an automatic night light using an LDR sensor can be a practical, economical, and simple choice for everyday use.